2021
DOI: 10.3126/njms.v6i2.42399
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori Infection Among Patients Undergoing Upper Gastrointestinal Endoscopy For Dyspepsia

Abstract: Introduction: Helicobacter pylori is associated with the pathogenicity of gastroduodenal mucosal lesions, ulcers, and gastric cancers. The present study was undertaken to study the prevalence of H. pylori infection among patients undergoing upper gastrointestinal (UGI) endoscopy for dyspepsia in the Nepalese population. Methods: A cross-sectional, hospital-based study was conducted among patients presenting with dyspepsia. Each study patient underwent upper gastrointestinal endoscopy followed by a rapid urea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…9 In this study, we found a higher female HP infection status over males unlike similar previous studies. 2,[10][11][12] This discrepancy could have been a result of study population as this current study included a higher number of female patients. On a global scenario, there are conflicting reports regarding gender predisposition to HP infection.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…9 In this study, we found a higher female HP infection status over males unlike similar previous studies. 2,[10][11][12] This discrepancy could have been a result of study population as this current study included a higher number of female patients. On a global scenario, there are conflicting reports regarding gender predisposition to HP infection.…”
Section: Discussionmentioning
confidence: 86%
“…1 The prevalence of HP has been reported to be around 30-65% using several diagnostic aids among the general Nepalese population. [2][3][4][5] In the present study, we aimed to find the incidence of HP in endoscopic biopsy among patients attending Gastro outpatient department (OPD) of Chitwan Medical College with symptoms of epigastric pain.…”
Section: Introductionmentioning
confidence: 99%